VALIDITY OF E-WORKSHEET REACTION RATE TO PRACTICE CRITICAL THINKING ABILITY USING PROBLEM BASED LEARNING MODEL - Damayanti, Vivi; Rahma, Eka Aprilia; Agustin, Liza Nurrahma Dwi; Novita, Dian (JCER (Journal of Chemistry Education Research), 2025)
This research aims to describe the validity of reaction rate electronic worksheets in training critical thinking skills with the problem based learning model developed. The development model in this research is 4-D (four-D) with the stages Define, Design, Develop and Disseminate. The subjects of this research were students of SMAN 7 Surabaya. The validation results will then be analyzed according to the mode of each aspect. Based on the validation results, it is known that the reaction rate electronic worksheet developed has a very valid category with a score of 4 in the content validity aspect and a valid category with a score of 3 in the construct validity aspect. Then the electronic worksheet can be used in the classroom learning process so that you can find out the practicality and effectiveness of the electronic reaction rate worksheet being developed.